Calculation of electromagnetic fields, forces and temperature in a finite cylinder - Buikis, A.; Kalis, H. (Mathematical Modelling and Analysis, 2002)
The distribution of electromagnetic fields, forces and temperatures induced by a three‐phase axially‐symmetric system of electric current in a conducting cylinder of a finite length has been calculated. An original method was used to calculate the radial and axial components of the magnetic fields and the mean values of electromagnetic forces, as well as the azimuthal component of the electric field and of the mean curl of the electromagnetic forces. For finding the source term in the temperature equation we applied an approximation of the heat transport problem based on the finite‐difference method. Such a procedure allows one to calculate the distribution of temperatures inside the cylinder depending on that of currents in the wires. Elektromagnetinių laukų, jėgų ir temperatūros skaičiavimas baigtiniame cilindre Santrauka. Apskaičiuojamas elektromagnetiniu laukų, jėgų ir temperatūrų pasiskirstymas trifazės elektros srovės ašinėje simetrinėje sistemoje baigtiniame cilindre. Panaudotas originalus metodas apskaičiuojant radialinę ir ašinę komponentes, vidurkines elektromagnetinių jėgų reikšmes, elektrinio lauko azimutinę komponentę ir elektromagnetinių jėgų rotorių. Temperatūros šaltinio nustatymui, naudojama šilumos laidumo uždavinio aproksimacija baigtinių skirtumų metodu. Tokia procedūra leidžia skaičiuoti temperatūros pasiskirstymą cilindro viduje, priklausomai nuo srovių jo paviršiuje. First Published Online: 14 Oct 2010